2018
DOI: 10.1007/s11356-018-1666-2
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory role of endogenous iron on greenhouse gas emissions under intensive nitrogen fertilization in subtropical soils of China

Abstract: Anaerobic batch experiments were conducted to study the regulatory role of endogenous iron in greenhouse gas emissions under intensive nitrogen fertilization in subtropical soils of China. Fe, Fe, and NO-N dynamics and NO, CH, and CO emissions, as well as the relationships between N fertilizer, endogenous iron, and greenhouse gas emissions were investigated. The emissions of NO increased to different extents from all the test soils by N1 (260 mg N kg) application compared with N0. After 24 days of anaerobic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Impacts of nFe 3 O 4 @DMSA and nFe 3 O 4 on gas production Iron oxides are regarded as important electron acceptors in subtropical soils, and organic C in soils might be anaerobically decomposed to CH 4 and CO 2 following the reduction of iron oxides. 29 Many studies have explored the effect of nFe 3 O 4 on CH 4 production, with the results aligning with the trend that nFe 3 O 4 stimulate the methanogenesis under the circumstances of anaerobic digestion, 30 wastewater plants, 31,32 and soil ecosystems. 4,11,33 However, this was not the case observed in this study showing the negligible changes in CH 4 production led by nFe 3 O 4 across all soils.…”
Section: Discussionmentioning
confidence: 73%
“…Impacts of nFe 3 O 4 @DMSA and nFe 3 O 4 on gas production Iron oxides are regarded as important electron acceptors in subtropical soils, and organic C in soils might be anaerobically decomposed to CH 4 and CO 2 following the reduction of iron oxides. 29 Many studies have explored the effect of nFe 3 O 4 on CH 4 production, with the results aligning with the trend that nFe 3 O 4 stimulate the methanogenesis under the circumstances of anaerobic digestion, 30 wastewater plants, 31,32 and soil ecosystems. 4,11,33 However, this was not the case observed in this study showing the negligible changes in CH 4 production led by nFe 3 O 4 across all soils.…”
Section: Discussionmentioning
confidence: 73%
“…For example, Fe (III) minerals and Fe complexed with SOM explained nitrous oxide (N2O) emissions across a set of agricultural soils; more than any other intrinsic soil property (Zhu et al, 2013). Similarly, Han et al (2018) found that soil Fe regulates N2O emissions.…”
mentioning
confidence: 89%
“…These reactions, which can occur through both chemical or microbial pathways, include chemo-denitrification (Burger and Venterea, 2011) and anaerobic ammonia oxidation coupled with Fe(III) reduction-Feammox (Wan et al, 2021). In addition, Fe is shown to affect rates of denitrification (Wang et al, 2016) and nitrification (Huang et al, 2016a) in experiments with both Fe addition and soil endogenous Fe (Han et al, 2018).…”
mentioning
confidence: 99%
“…Increasing evidence shows that Fe specifically represents a major control over N biological transformations, including mineralization (Wade et al, 2018), nitrification (X. Han et al, 2018), and denitrification (Wang et al, 2016;Zhu et al, 2014), as well as their abiotic analogous reactions, such as chemo-denitrification (Burger and Venterea, 2011) and Fe-mediated hydroxylamine (NH 2 OH) oxidation to nitrous oxide (N 2 O) (Bremner et al, 1980). These reac-I.…”
Section: Introductionmentioning
confidence: 99%